A new IoT system for non-contact body temperature sensing and warning - Akgun, Fatma Aydin; Soyturk, Giray; Dede, Muhtalip (YILDIZ TECHNICAL UNIV, 2023)
In this study we aim to monitor and analyze body temperature without using a camera, unlike existing products, using thermal, distance, humidity, and temperature sensors. With the devel-oped prototype and mobile application, the system provides emergency response by warning emergency response teams or family members who do not need to be in the same environ-ment as the patient in a dangerous body temperature. The system consists of two main parts. One of them is the cloud server layer, which includes the API layer developed with the mi-croservice architecture for database and data transport. The other is the internet layer, where components such as devices, mobile applications, and IoT Platforms are open to the internet. The prototype produced has practical use for individual use, for body temperature control in health institutions such as hospitals and public areas during epidemic processes.
Keywords: Internet of Things (IoT), Sensors; Machine Learning; Neural Network Algorithm; Engineering